2010
DOI: 10.1530/rep-10-0076
|View full text |Cite
|
Sign up to set email alerts
|

Follicle growth and oocyte development after ovary transplantation into back muscle of immune-intact adult castrated male mice

Abstract: Ovary grafting is not only a method of investigating follicle and oocyte development, but also a useful model to explore the possibility of the re-establishment of the reproductive axis in male-to-female sexual reversal. This study investigated ovary survival and follicle development after mouse ovaries were transplanted into immune-intact castrated male mice. Ten-day-old mouse ovaries were transplanted into the back muscle of adult outbred castrated male mice treated with immunosuppressants. Twenty-two days l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 71 publications
(100 reference statements)
2
14
0
Order By: Relevance
“…E 2 and P 4 are the most representative steroids (Li et al 2010). In this study, the mean serum concentration of E 2 increased significantly in the autografted EPO-treated group.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…E 2 and P 4 are the most representative steroids (Li et al 2010). In this study, the mean serum concentration of E 2 increased significantly in the autografted EPO-treated group.…”
Section: Discussionsupporting
confidence: 55%
“…We also chose the back muscle site, as more rapid revascularization occurs in an i.m. transplantation site than in other graft sites (Israely et al 2003, Soleimani et al 2008, Dath et al 2010, Li et al 2010, Commin et al 2012.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Ovariectomy was carried out through bilateral incisions on each side of the spinal column in the dorsal body wall. A small incision (0.5 cm) was made along the right and left gluteus superficialis muscle fibres, and the excised ovaries were autografted immediately into the gluteal muscles as the transplantation site as multiple reports have documented the effect of intramuscular transplantation on increasing follicular development and survival rate and fast vascularization (Abir et al, 2011;Dath et al, 2010;Friedman et al, 2012;Li et al, 2010;Soleimani et al, 2008. In addition, Israely et al (2003) compared the efficacy of two transplantation sites (subcutaneous and intramuscular), which found that intramuscular grafts recovered and resembled normal ovaries; however, most of the subcutaneous grafts remained impaired and necrotic (Israely et al, 2003).…”
Section: Ovarian Autotransplantation and N-acetylcysteine Treatmentmentioning
confidence: 99%
“…In all treatment groups at day 14 after transplantation there was an increase in the number of functional corpora lutea, but this was significant just in the group treated with NAC150 (p=0.02 . Li et al 28 also describe an elevation of estradiol levels studying follicular growth and oocyte development after transplantation in muscle of spayed male mice.…”
Section: Discussionmentioning
confidence: 99%